Safety, Acceptability and Efficacy of Periconal as Compared Retrobulbar Anesthesia in Cataract Surgery - Rao Rashad Qamar, Mazhar-u-Zaman Soomro, Imran Attaullah (Pakistan Journal of Ophthalmology, 2007)
Purpose: To assess the safety, acceptability and effectiveness of periconal versus retro bulbar along with facial anesthesia in cataract surgery. Material and Method: A prospective, comparative study was designed to find out the safety, acceptability and effectiveness of periconal (transconjunctival route) and retro bulbar along with facial block for patients undergoing cataract surgery. One hundred and fifty patients were included in this study. The patients were divided in two equal groups. One group received periconal block (transconjunctival route) while other facial along with retro bulbar block. The anesthetic used was a mixture of Xylocaine and bupivacaine in equal proportion. The quantity used was 3 ml for group A and 7-10 ml for group B. A questionnaire was filled for all patients and analyzed to compare two groups. Results: Total 150 patients were divided in two equal groups. Group A; 72 patients were comfortable at the time of injection while in Group B, 71 patients complained of pain. As for as anesthesia, akinesia and analgesia are concerned, results are comparable. Conclusion: By analyzing the facts and figures in our study, we came to conclusion that periconal anesthesia (transconjunctival route) is an effective, acceptable and safe approach for anesthesia, akinesia and pain at the time of injection and during the surgery.